Instant messaging and presence technologies for college campuses. - Chatterjee, S.
Instant messaging is an application that enables networked users to send and receive short messages. Presence provides information about users' reachability and willingness to accept/reject a brief chat session. Various proprietary IM and presence (IM&P) solutions are currently on the market, and standards are emerging. There are interoperability problems between the two dominant standards (SIMPLE and XMPP); as a result, this important application is finding difficulty in widespread deployment within college campuses and businesses. We describe a brief history of the development of IM&P technology discuss the current standardization work being done within IETF, and present an overall architecture of emerging standards. We provide a comparison between the SIP/SIMPLE and Jabber/XMPP standards. We also present data and its analysis from a survey of campus organizations that sheds light into the main issues of deploying, managing and provisioning of IM&P services on college campus.
Keywords: IM&P technology; Internet Engineering Task Force; Jabber/XMPP standard; SIP/SIMPLE standard; Brief chat session; Instant messaging; Interoperability problems; Short messages